Para una teoría del conocimiento - Falcón y Tella, Fernando (FORO. Revista de Ciencias Jurídicas y Sociales, Nueva Época, 2004)
This article follows a three-dimensional perspective which distinguishes among values, norms and facts. From this point of view it studies the three forms of access to knowledge in general —Theology, Philosophy and Science—, and, more especially, to legal understanding —Legal Philosophy, Legal Dogmatics and the Sociology of Law— and to legal-philosophical knowledge.